2008
DOI: 10.1200/jco.2007.14.2091
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Adrenalectomy for Isolated Synchronous Versus Metachronous Adrenal Metastases in Non–Small-Cell Lung Cancer: A Systematic Review and Pooled Analysis

Abstract: For an isolated adrenal metastasis from NSCLC, patients with a synchronous metastasis who underwent adrenalectomy had a shorter median overall survival than those with a metachronous metastasis. However, a durable long-term survival is achieved in approximately 25% in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
189
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(214 citation statements)
references
References 25 publications
13
189
0
12
Order By: Relevance
“…It was possible to extract some data from the included studies to compare these outcomes, but no statistically significant difference could be demonstrated between the two groups. In general, metastasectomies for synchronous metastases are associated with shorter median survival than resection of metachronous metastases; this has been shown in the case of hepatectomy for colorectal metastases [28,29], pulmonary resection for RCC metastases [30] and adrenalectomy for metastatic non-small-cell lung cancer [31]. The previously-mentioned review of case reports and series of pancreatectomy for metastatic RCC suggest that the same principle applies [27]; our data are not consistent with this, but a dedicated study looking specifically at this question remains to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible to extract some data from the included studies to compare these outcomes, but no statistically significant difference could be demonstrated between the two groups. In general, metastasectomies for synchronous metastases are associated with shorter median survival than resection of metachronous metastases; this has been shown in the case of hepatectomy for colorectal metastases [28,29], pulmonary resection for RCC metastases [30] and adrenalectomy for metastatic non-small-cell lung cancer [31]. The previously-mentioned review of case reports and series of pancreatectomy for metastatic RCC suggest that the same principle applies [27]; our data are not consistent with this, but a dedicated study looking specifically at this question remains to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study from centres in the USA, RAZ et al [161] reported a 5-year survival of 34% following excision of solitary adrenal metastasis. Patients with a synchronous metastasis usually have a shorter survival than those presenting with metachronous metastasis [166,167]. However, a durable long-term survival is achievable in both groups of patients (,25% at 5-years) [166].…”
Section: Surgery For Stage IV Lung Cancer (Solitary Metastasis)mentioning
confidence: 99%
“…Patients with a synchronous metastasis usually have a shorter survival than those presenting with metachronous metastasis [166,167]. However, a durable long-term survival is achievable in both groups of patients (,25% at 5-years) [166].…”
Section: Surgery For Stage IV Lung Cancer (Solitary Metastasis)mentioning
confidence: 99%
“…Tanvetyanon et al, demonstrated 5-year survival rates of 25% following resection of isolated synchronous adrenal metastases and reported 26% after resection of metachronous adrenal metastases in their study conducted on NSCLC patients developing solitary adrenal metastasis [4]. Conducted studies revealed that the rate of complication was 9-20% in patients having adrenalectomy for solitary adrenal metastasis [2][3][4]7].In recent years, the use of radiotherapy, which is a treatment modality as effective as surgical resection, has become prevalent for the management of oligometastases. Today, three different modalities have been tested in the radiotherapy treatment of adrenal gland metastases.…”
mentioning
confidence: 99%
“…They can be functional or non-functional. Major treatment methods used fort he treatment of adrenal gland primary tumors or metastases are surgery, arterial embolisation, chemical ablation, radiofrequency ablation and radiotherapy [1][2][3][4].…”
mentioning
confidence: 99%